2009
DOI: 10.1007/bf03182294
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and thigmotropism in the lichen symbiosis: A reappraisal

Abstract: The development of many complex stratified lichen thalli is made through stages of complex phenotypic interactions between a filamentous fungus (the rnycobiont), and a trebouxioid alga (the photobiont). Typically, the second stage of this symbiotic development is marked by the envelopment of the photobiont by the mycobiont through increased lateral hyphal branching and the formation of appressoria, Previously, the mycobiont's envelopment of photobiont cells was considered thigmotropic (a growth response due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…A parasitic stage was also hypothesized early on for mycobiont mycelia growing on moss protonemata, before the establishment of the symbiosis with their algal photobionts (Bonnier 1889). However, the growth, in the laboratory, of the mycobionts of Cladonia foliacea and C. grayi on protonemata does not lead to the formation of appressoria or an increase in hyphal lateral branching, which characterize the early contact stages of fungi with symbiotic green algae, and the growth of protonemata slows down only upon incubation with C. foliacea (Giordano et al 1999;Joneson and Lutzoni 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A parasitic stage was also hypothesized early on for mycobiont mycelia growing on moss protonemata, before the establishment of the symbiosis with their algal photobionts (Bonnier 1889). However, the growth, in the laboratory, of the mycobionts of Cladonia foliacea and C. grayi on protonemata does not lead to the formation of appressoria or an increase in hyphal lateral branching, which characterize the early contact stages of fungi with symbiotic green algae, and the growth of protonemata slows down only upon incubation with C. foliacea (Giordano et al 1999;Joneson and Lutzoni 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the in vitro and in situ resynthesis between lichen symbionts have provided a better understanding of the cellular changes during the interaction (Ahmadjian et al 1980;Bubrick et al 1985;Ott 1987a;Galun and Garty 1988;Stocker-Wörgötter and Türk 1991;Jahns 1993;Kon et al 1993;Stocker-Wörgötter 1995;Schaper and Ott 2003;Joneson and Lutzoni 2009;Athukorala et al 2014a). Cell characteristics of the co-inoculated symbionts in species of Xanthoria and Cladonia have been described for five stages of the interaction: a "pre-contact" stage shows symbionts which are not in physical contact but are close enough to share extracellular excretions; a "contact" stage shows the alga and fungus beginning to make physical contact by appressorial-like structures; a "growth together" stage shows the coordinated growth of the symbionts forming a cellular mass; a "transitional pre-thallus" stage shows the formation D r a f t of an undifferentiated thallus-like structure; and finally the production of a stratified thallus (Ahmadjian et al 1978;Galun 1988;Armaleo 1991).…”
Section: Isolation and Culturing Of Symbiontsmentioning
confidence: 99%
“…The understanding of processes has been improved, including the role of lichen lectins and other molecules in the recognition of compatible algal partners (Molina et al 1993;Athukorala et al 2015), gene expression in both partners during the symbiont interaction (Joneson et al 2011;Athukorala et al 2015;Hametner and StockerWörgötter 2015), and mechanisms for drought tolerance in lichens (Honegger 1996) under controlled conditions. Recognition between cells of the symbionts is the first step in the association, which was examined by Joneson and Lutzoni (2009) Ott (1987a) indicates that extensive mucilage production is a vital characteristic during the resynthesis of Xanthoria parietina and Fulgensia bracteata (Schaper and Ott 2003). Protein binding to the symbiotic algae was recognized in early studies (Bubrick and Galun 1980;Bubrick et al 1981) where it was hypothesized to play a role in recognition between the symbionts.…”
Section: R a F T 11mentioning
confidence: 99%
“…The macrolichen thallus is comprised of differentiated "tissues" arranged in layers (see section 2) that often produce different metabolites (see Honegger (2008) for a review of morphogenesis in lichens). Thallus development in lichens has been examined using microscopy (Honegger, 1990;1993;Joneson & Lutzoni, 2009) and recently a study has described a number of genes that correlate with symbiont recognition and early thallus development (Joneson et al, 2011). Observations of cultures of lichen-forming fungi have suggested that thallus development may be involved in production of secondary metabolites.…”
Section: Environmental Cues Affecting Secondary Metabolite Productionmentioning
confidence: 99%